Systematic review of shared decision-making in surgery. Issue 13 (25th October 2018) - de Mik, S M L; Stubenrouch, F E; Balm, R; Ubbink, D T
Abstract: Background: Multiple treatment options are generally available for most diseases. Shared decision-making (SDM) helps patients and physicians choose the treatment option that best fits a patient's preferences. This review aimed to assess the extent to which SDM is applied during surgical consultations, and the metrics used to measure SDM and SDM-related outcomes. Methods: This was a systematic review of observational studies and clinical trials that measured SDM during consultations in which surgery was a treatment option. Embase, MEDLINE and CENTRAL were searched. Study selection, quality assessment and data extraction were conducted by two investigators independently. Results: Thirty-two articles were included. SDM was measured using nine different metrics. Thirty-six per cent of 13 176 patients and surgeons perceived their consultation as SDM, as opposed to patient- or surgeon-driven. Surgeons more often perceived the decision-making process as SDM than patients (43·6 versus 29·3 per cent respectively). SDM levels scored objectively using the OPTION and Decision Analysis System for Oncology instruments ranged from 7 to 39 per cent. Subjective SDM levels as perceived by surgeons and patients ranged from 54 to 93 per cent. Patients experienced a higher level of SDM during consultations than surgeons (93 versus 84 per cent). Twenty-five different SDM-related outcomes were reported. Conclusion: At present, SDM in surgery is still in its infancy, although surgeons and patients both think of it favourably. Future studies should evaluate the effect of new interventions to improve SDM during surgical consultations, and its assessment using available standardized and validated metrics. Abstract : Heterogeneous data